Effect of Multi-Source Ultrasonic on the Microstructure and Mechanical Properties of a Large Scale 2219 Al Alloy Ingot During Casting - Li, Anqing; Jiang, Ripeng; Liu, Zhilin; Li, Ruiqing; Zhang, Yun (Frontiers in Materials, 2022)
High-energy ultrasonic vibration is found as an effective approach that can dramatically improve the performance of large-scale ingot. In this work, it was applied to manufacture the large 2219 aluminum (Al) alloy ingot (630 mm in diameter and 4500 mm in length). The degassing efficiency, the average size change of α-Al grains and morphology change of Al2Cu precipitated phase under double-source ultrasound (DSU) and three-source ultrasound (TSU) were compared. Meanwhile, the influence of ultrasonic field on the macroscopic segregation of Cu content and mechanical properties were investigated. It was found that the degassing efficiency of TSU appeared significantly higher. The results also indicated that α-Al grains of the ingot could get refiner under the TSU technology from the center to the edge part, and the distribution of macroscopic Cu content was more uniform, and the area fraction of the Al2Cu phase was decreased more. The mechanical properties of the ingot were superior to samples with DSU technology. Furthermore, it was demonstrated that the stress concentration of the coarse Al2Cu phase at the center of the DSU process leads to the deterioration of the mechanical properties.